Comparison Analysis of Quality of Ax-7 Advance Shelling Lubricants and Pertamina Enduro Racing Lubricants on Kawasaki Ninja 250cc Injeksi Motor - Putra, Theo Agytha (Universitas Mercu Buana, 2018)
Abstract - An analysis of the degradation of the quality of lubricating oil in motorized vehicles has been carried out. In this study 4tak motorcycles were used, namely the 2016 Kawasaki Ninja 250cc Injection motorbike with two different lubricants and lubricants used, namely the Ax 7 and Enduro racing Shell Advance with SAE 10W40. Parameters that will be analyzed are viscosity, Water content, Wear metal and a reduction in TBN value with the lab testing method in addition to lubricant testing and also testing the performance of the engine using both of these oils using a dyno test and for fuel consumption testing using a road test. Testing the value of viscosity, water content, wear metal and decreasing the value of TBN. Lab tests were conducted to determine the value of viscosity, contamination of water, wear on the vehicle engine and a decrease in the value of TBN by taking samples of oil that has been used for about 2000 km, this lab test aims to predict the cleanliness of the combustion chamber, contamination of water and view equipmen which wear occurs so that it can prevent more fatal damage. From the three tests, it was found that using Shell Advance Ax 7 oil was better than using Enduro Racing oil.